2022
DOI: 10.1142/s0192415x22500331
|View full text |Cite
|
Sign up to set email alerts
|

Hydroxysafflor Yellow A Alleviates Ischemic Stroke in Rats via HIF-1α, BNIP3, and Notch1-Mediated Inhibition of Autophagy

Abstract: Stroke has become a major cause of death and disability worldwide. The cellular recycling pathway autophagy has been implicated in ischemia-induced neuronal changes, but whether autophagy plays a beneficial or detrimental role is controversial. Hydroxysafflor Yellow A (HSYA), a popular herbal medicine, is an extract of Carthamus tinctorius and is used to treat ischemic stroke (IS) in China. HSYA has been shown to prevent cardiovascular and cerebral ischemia/reperfusion injury in animal models. However, the spe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 28 publications
0
7
0
Order By: Relevance
“…(Pan et al, 2021). The underlying mechanisms of HIF-1 regulated stroke including apoptotic (Cheng et al, 2014), neurogenesis (Wu et al, 2018), BBB integrity (Liu et al, 2021b) inflammation (Pan et al, 2021), autophagy (Xie et al, 2022;Zhang et al, 2022), and oxidative stress (Peng et al, 2020). However, the effect of HIF-1 was doublesided and may be related to the time and degree of ischemia.…”
Section: Discussionmentioning
confidence: 99%
“…(Pan et al, 2021). The underlying mechanisms of HIF-1 regulated stroke including apoptotic (Cheng et al, 2014), neurogenesis (Wu et al, 2018), BBB integrity (Liu et al, 2021b) inflammation (Pan et al, 2021), autophagy (Xie et al, 2022;Zhang et al, 2022), and oxidative stress (Peng et al, 2020). However, the effect of HIF-1 was doublesided and may be related to the time and degree of ischemia.…”
Section: Discussionmentioning
confidence: 99%
“…In MCAO rats, Qi et al (2014) found that HSYA promoted autophagy in the penumbra through activating AKT-dependent autophagy pathway, which was subsequently verified as a potential mechanism in the HSYA-mediated neuroprotection. In contrast, Yang et al (2018) ; Zhang et al (2022) observed that HSYA inhibited autophagy following ischemia for exerting neuroprotection in OGD/R-insulted BMECs and MCAO rats, which is inconsistent with the observation of Qi et al A body of studies has demonstrated that autophagy increases in cerebral I/R injury, and both harmful and protective potentials of autophagy have been reported ( Wang et al, 2013 ; Luo et al, 2014 ). Yang et al (2018) found that HSYA suppressed excessive autophagy evoked by OGD/R injury in BMECs and such inhibition was partially associated with the activation of Class I PI3K/AKT/mTOR pathway.…”
Section: Protective Effects and Mechanismsmentioning
confidence: 78%
“… Yang et al (2018) found that HSYA suppressed excessive autophagy evoked by OGD/R injury in BMECs and such inhibition was partially associated with the activation of Class I PI3K/AKT/mTOR pathway. Similarly, Zhang et al (2022) revealed that HSYA suppressed autophagy induced by brain ischemia probably through limiting the expressions of HIF-1, BNIP3 and Notch 1. All together, these results demonstrate that HSYA may regulate autophagy induced by cerebral I/R injury via activating AKT-related pathway and the Class I PI3K/AKT/mTOR pathway, as well as decreasing the expressions of HIF-1, BNIP3 and Notch 1.…”
Section: Protective Effects and Mechanismsmentioning
confidence: 95%
“…Hypoxia-inducible factor-1 alpha (HIF-1α) is a sensitive regulator of oxygen homeostasis and plays divergent roles in the pathophysiology of IS, which is sophisticatedly regulated by the spatiotemporal expression [ 38 ]. Recent studies showed that elevated HIF-1α level compromised BBB integrity in the acute phase of IS through tight junctions (TJs) alterations in hypoxic conditions [ [39] , [40] , [41] ]. Consistent with previous reports, significantly elevated expression of HIF-1α was observed in tMCAO rats after 72 ​h reperfusion, which was 2-fold that of the sham group ( Fig.…”
Section: Resultsmentioning
confidence: 99%